2020
DOI: 10.1200/jco.2020.38.4_suppl.578
|View full text |Cite
|
Sign up to set email alerts
|

Primary versus metastatic intrahepatic cholangiocarcinoma: A comparative comprehensive genomic profiling (CGP) study.

Abstract: 578 Background: Genomic alterations (GA) characteristic of IHCC are well known. We queried whether the GA of IHCC from primary tumor biopsies (p-bx) would differ from IHCC metastasis biopsies (m-bx). Methods: CGP was performed on 1,268 cases of advanced stage IHCC using p-bx in 1,048 cases and m-bx from 220 cases. Tumor mutational burden (TMB) was determined on 0.8-1.1 Mbp of sequenced DNA and microsatellite instability (MSI) was determined on 114 loci. PD-L1 expression in tumor cells (Dako 22C3) was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Evidence supporting this was provided by a larger comparative comprehensive genomic profiling study, which demonstrated that the frequency of KRAS mutations was significantly (approximately twofold) greater in metastasis versus primary tumor biopsies. 33 However, contrary to these findings, a recent NGS study did not find any significant differences in the frequencies of genetic alterations in primary tumor biopsies (n ¼ 141) versus metastasis biopsies (n ¼ 54). 24 Of note, FGFR2 fusions have been reported to occur in surgical resections from patients with early-stage CCA, indicating that FGFR2 fusions may occur early in oncogenesis and may drive subsequent disease progression.…”
Section: Frequently Altered Genesmentioning
confidence: 73%
See 2 more Smart Citations
“…Evidence supporting this was provided by a larger comparative comprehensive genomic profiling study, which demonstrated that the frequency of KRAS mutations was significantly (approximately twofold) greater in metastasis versus primary tumor biopsies. 33 However, contrary to these findings, a recent NGS study did not find any significant differences in the frequencies of genetic alterations in primary tumor biopsies (n ¼ 141) versus metastasis biopsies (n ¼ 54). 24 Of note, FGFR2 fusions have been reported to occur in surgical resections from patients with early-stage CCA, indicating that FGFR2 fusions may occur early in oncogenesis and may drive subsequent disease progression.…”
Section: Frequently Altered Genesmentioning
confidence: 73%
“…13 Of note, the comparative comprehensive genomic profiling study described above demonstrated that among actionable genetic alterations in metastasis versus primary tumor biopsies, respectively, the KRAS G12C mutation was significantly more frequent, whereas IDH1 mutations and FGFR2 alterations were significantly less frequent. 33 Because IDH1 and FGFR2 alterations are highly characteristic of iCCA, the authors concluded that the metastasis biopsies assessed may have included metastatic lesions derived from primary tumors that had been misclassified as iCCA. 33…”
Section: Clinically Actionable Genetic Alterationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Robust evidence supporting the universal use of circulating tumor DNA (ctDNA) for iCCA is currently limited, but recent analyses have highlighted its potential to identify actionable alterations in iCCA [ 74 , 75 , 76 ]. Moreover, the sensitivity of liquid biopsy tests to detect fusions/rearrangements, such as FGFR2 fusions, may be limited compared to tumor tissue [ 74 , 75 , 77 , 78 ]. Although the utilization of ctDNA is an attractive alternative to invasive procedures, its detection of biomarker alterations in iCCA needs further development.…”
Section: Identifying Potential Challenges and Solutions For Optimal Treatment Of Patients With Iccamentioning
confidence: 99%
“…58 In a recent report of a retrospective analysis comparing CGP from primary biopsies of IHCCA to the metastatic ones in 1268 samples, although many findings were common, some of them such as IDH1 mutations and FGFR2 fusion were significantly more frequent in the primary site. 59 The authors concluded that this was suggestive of a wrong primary diagnosis in the metastatic samples. PATIENTS Publication of the results of the ClarIDHy, the first positive randomised trial for a targeted therapy (using the IDH1 inhibitor IVOSIDENIB in CCA patients with an IDH1 mutation), has opened the pathway not only for using this targeted therapy in a selected group of patients (very recently approved by FDA) but also for doing molecular testing in every advanced CCA patient candidate to systemic treatment, especially in intrahepatic CCA.…”
Section: Idh1 Mutati On S In Chol Ang Ioc Arcinomamentioning
confidence: 99%